Is Domestic Abuse an Adult Social Work Issue?. Issue 2 (17th February 2016) - Robbins, Rachel; Banks, Concetta; McLaughlin, Hugh; Bellamy, Claire; Thackray, Debbie
Abstract: Within a global profession with a stated definition that includes 'promoting social change and development, social cohesion and the empowerment and liberation of people' (online), it would be expected that the issue of domestic abuse would be integral to the training and role of all social workers. This article reports on research, which highlighted both a lack of understanding of the role of adult social worker within cases of domestic abuse and also a desire for further training around the issue. However, this article sets out how the current UK (in particular, English) context of social work marginalises the issue of domestic abuse within practice with adults. This marginalisation has been achieved through the construction of domestic abuse as a children and families issue and limited duties, powers and resources within statutory work to support victims/survivors in their own right, rather than as 'failing' parents. However, the article argues that the role of social work education should be wider than teaching to the current policy or procedures and instead encourage a wider appreciation of the social, historical and political context. The article concludes with tentative suggestions for how domestic abuse could be considered within the social work curriculum for adult practitioners. This is in acknowledgement that social workers can be well positioned for the detection, investigation and support of those experiencing abuse.